2022
DOI: 10.1111/een.13146
|View full text |Cite
|
Sign up to set email alerts
|

Ant nest distribution and richness have opposite effects on a Neotropical plant with extrafloral nectaries

Abstract: Studies assessing the effects of the spatial distribution of ant nests on ant‐plant mutualisms are rare, even though they could be decisive to the outcomes of such interactions. Here, we investigated how ant nest abundance and richness affected a Neotropical plant with extrafloral nectaries (EFN), Smilax polyantha (Smilacaceae). We used baits to sample all nests of mutualistic ants within a 12 m radius of each plant. All neighbouring plants with EFN within 10 m of each tagged plant were also sampled. We measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
4
0
1
Order By: Relevance
“…If the density of ant nests is higher near EFN plants, this could further contribute to facilitation by increasing soil fertility (Wagner & Nicklen, 2010). In addition to the spatial arrangement of ant nests (Moura et al, 2022), the outcome of the interaction between EFN plants and ants also depends on ant identity, as species attracted to nectar differ in their defense ability (Fagundes et al, 2017).…”
Section: Facilitation May Be Driven By Efn-associated Antsmentioning
confidence: 99%
“…If the density of ant nests is higher near EFN plants, this could further contribute to facilitation by increasing soil fertility (Wagner & Nicklen, 2010). In addition to the spatial arrangement of ant nests (Moura et al, 2022), the outcome of the interaction between EFN plants and ants also depends on ant identity, as species attracted to nectar differ in their defense ability (Fagundes et al, 2017).…”
Section: Facilitation May Be Driven By Efn-associated Antsmentioning
confidence: 99%
“…This same pattern has been reported in other studies [91,92], where the authors suggest that resource, space, or time limitations may reduce the interaction capacity of some species. Moura et al (2022) [93] also found negative associations between ant nest richness and the herbivory rate of EFNs' bearing plants. These authors suggest that intensified competition due to high nest richness may distract visiting ants from the presence of herbivores on the plants.…”
Section: Effectiveness Of Ant Predatory Behaviormentioning
confidence: 88%
“…Areas where C . brasiliense was sampled sustains several other EFN–plant species (Sendoya et al 2009, Lange et al 2013, Moura et al 2022). The other top-studied plants such as Qualea , Banisteriopsis and Ouratea also occur in a community with several other EFN–plants.…”
Section: Discussionmentioning
confidence: 99%
“…Fabaceae shared six species with other biomes, while Bignoniaceae and Euphorbiaceae shared one (Figure 9). species (Sendoya et al 2009, Lange et al 2013, Moura et al 2022. The other top-studied plants such as Qualea, Banisteriopsis and Ouratea also occur in a community with several other EFN-plants.…”
Section: Network Analysesmentioning
confidence: 99%